Penggunaan Dana Desa terhadap Pemberdayaan dalam Meningkatkan Kesejahteraan Masyarakat di Desa Wolowea Timur Kecamatan Boawae Kabupaten Nagekeo - Maria Liliosa Coo Wea; Petrus I. De Rozari; Cicilia A. Tungga (Journal Of Business, Finance, and Economics (JBFE), 2024)
This study aims to determine the use of village funds for empowerment in improving community welfare in East Wolowea Village, Boawae District, Nagekeo Regency by using a qualitative descriptive approach method. The type of research used in this study is field research. The informants used in this study consisted of the Village Head, Village Secretary, Village Treasurer, BPD and the Community. Data were collected using observation, interview, and documentation techniques. The data sources in this study are primary data sources and secondary data. Based on the results of the research, it shows that the empowerment program given to the community in East Wolowea Village, through assistance in the procurement of chickens, cocoa seedlings, and plant seeds has had a positive impact on the welfare of the community. These positive impacts can be seen in increasing income, fulfilling nutritional needs, and saving costs. However, the overall improvement in welfare is still not significant due to several obstacles faced, such as changes in the number of uncertain crops and damage to crops.